Fertile Soil for Structural Funds? - Sjef Ederveen; Henri L.F. de Groot; Richard Nahuis (Tinbergen Institute, 2002)
Structural funds are the most intensively used policy instrument by the EuropeanUnion to promote economic growth in its member states and to speed up the process ofconvergence. This paper empirically explores the effectiveness of European Structural Fundsby means of a panel data analysis for 13 countries in the European Union. We show that – onaverage – Structural Funds are ineffective. For countries with the `right' institutions,however, Structural Funds are effective. The latter result is obtained for a wide range ofconditioning variables, such as openness, institutional quality, corruption and indicatorsfor good governance.
Keywords: F35; F36; O11; O40; O52; R58; 330; European Cohesion Policy; policy effectiveness; economic growth; European Union.; EU-Strukturfonds; Institutionelle Infrastruktur; Wirkungsanalyse; EU-Staaten